Frontispiece: Sugar–Protein Connectivity Impacts on the Immunogenicity of Site‐Selective Salmonella O‐Antigen Glycoconjugate Vaccines. Issue 45 (26th October 2015) - Stefanetti, Giuseppe; Hu, Qi‐Ying; Usera, Aimee; Robinson, Zack; Allan, Martin; Singh, Alok; Imase, Hidetomo; Cobb, Jennifer; Zhai, Huili; Quinn, Douglas; Lei, Ming; Saul, Allan; et al.
Abstract : Glycoproteins In their Communication onpage 13198 ff., Q.‐Y. Hu, F. Micoli et al. present two methods for the preparation of glycoconjugate vaccines with one single sugar chain linked to one or two positions of a carrier protein.